2016
DOI: 10.1530/ec-16-0024
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone deficiency during young adulthood and the benefits of growth hormone replacement

Abstract: Until quite recently, the management of children with growth hormone deficiency (GHD) had focussed on the use of recombinant human GH (rhGH) therapy to normalise final adult height. However, research over the past two decades that has demonstrated deficits in bone health and cardiac function, as well as impaired quality of life in adults with childhood-onset GHD (CO-GHD), has questioned this practice. Some of these studies suggested that there may be short-term benefits of rhGH in certain group of adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 70 publications
0
20
0
3
Order By: Relevance
“…*Studijska grupa za tranziciju pacijenata sa nedostatkom hormona rasta (azbučno): Bajkin Ivana 8,10 , Bojić Vladimir 4 , Vorgučin Ivana 9,10 , Dautović Slavica 9,10 , Đukić Aleksandar 11,13 , Živić Saša 5,7 , Katanić Dragan 9,10 , Lešović Snežana 14 , Marković Slavica 12,13 , Marinković Snežana 14 , Medić Milica 8,10 , Miljić Dragana 1,3 , Pekić Sandra 1,3 , Petakov Milan 1,3 , Sajić Silvija 3,4 , Soldatović Ivan 4,15 , Stanković Sandra 5 , Stojanović Marko 1,3 , Radenković Saša 6,7 , Radojković Danijela 6,7 , Cvetković Vesna 5 , Šaranac Ljiljana 5,7 1 Odeljenje za neuroendokrinologiju, Klinika za endokrinologiju, dijabetes i bolesti metabolizma, Klinički centar Srbije; 2 Оdeljenje za ispitivanje i lečenje žlezda sa unutrašnjim lučenjem, Institut za zdravstvenu zaštitu majke i deteta "Dr Vukan Čupić"; 3 Medicinski fakultet Univerziteta u Beogradu; 4 Tiršova univerzitetska dečja klinika; 5 Odeljenje endokrinologije, Klinika za dečje interne bolesti, Klinički centar Niš; 6 Klinika za endokrinologiju, Klinički centar Niš; 7 Medicinski fakulet Univerziteta u Nišu; 6 bolničkim uslovima na odeljenju "odrasle" endokrinologije. Tada poneti uput za hospitalizaciju, dobijen od nadležnog lekara iz Doma zdravlja.…”
Section: Smernice Za Prelazak Pacijenata Sa Nhr Od Pedijatra Endokrinunclassified
See 3 more Smart Citations
“…*Studijska grupa za tranziciju pacijenata sa nedostatkom hormona rasta (azbučno): Bajkin Ivana 8,10 , Bojić Vladimir 4 , Vorgučin Ivana 9,10 , Dautović Slavica 9,10 , Đukić Aleksandar 11,13 , Živić Saša 5,7 , Katanić Dragan 9,10 , Lešović Snežana 14 , Marković Slavica 12,13 , Marinković Snežana 14 , Medić Milica 8,10 , Miljić Dragana 1,3 , Pekić Sandra 1,3 , Petakov Milan 1,3 , Sajić Silvija 3,4 , Soldatović Ivan 4,15 , Stanković Sandra 5 , Stojanović Marko 1,3 , Radenković Saša 6,7 , Radojković Danijela 6,7 , Cvetković Vesna 5 , Šaranac Ljiljana 5,7 1 Odeljenje za neuroendokrinologiju, Klinika za endokrinologiju, dijabetes i bolesti metabolizma, Klinički centar Srbije; 2 Оdeljenje za ispitivanje i lečenje žlezda sa unutrašnjim lučenjem, Institut za zdravstvenu zaštitu majke i deteta "Dr Vukan Čupić"; 3 Medicinski fakultet Univerziteta u Beogradu; 4 Tiršova univerzitetska dečja klinika; 5 Odeljenje endokrinologije, Klinika za dečje interne bolesti, Klinički centar Niš; 6 Klinika za endokrinologiju, Klinički centar Niš; 7 Medicinski fakulet Univerziteta u Nišu; 6 bolničkim uslovima na odeljenju "odrasle" endokrinologije. Tada poneti uput za hospitalizaciju, dobijen od nadležnog lekara iz Doma zdravlja.…”
Section: Smernice Za Prelazak Pacijenata Sa Nhr Od Pedijatra Endokrinunclassified
“…*Study Group for GH treatment in transitional period (alphabetically):Bajkin Ivana 8,10 , Bojić Vladimir 4 , Vorgučin Ivana 9,10 , Dautović Slavica 9,10 , Đukić Aleksandar 11,13 , Živić Saša 5,7 , Katanić Dragan 9,10 , Lešović Snežana 14 , Marković Slavica 12, 13 , Marinković Snežana 14 , Medić Milica 8,10 , Miljić Dragana 1,3 , Pekić Sandra 1,3 , Petakov Milan 1,3 , Sajić Silvija 3,4 , Soldatovic Ivan 4,15 , Stanković Sandra 5 , Stojanović Marko 1,3 , Radenković Saša 6,7 , Radojković Danijela 6,7 , Cvetković Vesna 5 , Šaranac Ljiljana 5,7 1 Department for neuroendocrinology, Clinic for endocrinology, diabetes and metabolic diseases, Clinical Centre of Serbia; 2 Endcrinology department, Insittute for healthcare of mother and child "Dr Vukan Čupić"; 3 Medical Faculty, University of Belgrade 4 Tiršova University pediatric Clinic; 5 Department of endocrinology, Clinic for pediatric internal medicine, Clinical Centre Niš 6 Clinic for Endocrinology, Clinical Centre Niš; 7 Medical Faculty, University of Niš; 6 Clinic for endocrinology, diabetes and metabolic diseases, Clinical Centre of Vojvodina, Novi Sad; 9 Institute for health care of children and youth of Vojvodina -Department of Endocrinology, Clinical Center of Vojvodina, Novi Sad; 10 Medical Faculty, University of Novi Sad; 11 Center for Endocrinology, diabetes and metabolic diseases, Clinical Centre Kragujevac; 12 Pediatrics Clinic, Clinical Centre Kragujevac; 13 Faculty of medical sciences University of Kragujevac; 14 Special hospital for thyroid diseases and metabolic diseases "Zlatibor"; 15 Institute for Medical statistics and informactics, Belgrade and be available for the investigation during the morning hours until 12h. In this way patient would be free of commitments in the afternoon until the next morning.…”
Section: Guidelines For Ghd Patient Transition From a Pediatric Endocmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of human recombinant GH (rhGH) replacement therapy in improving height in children with GH deficiency (GHD) are well recognized (3). RhGH therapy can also improve body composition, lipid profile and bone mineral density (4). With regards to carbohydrate metabolism, observational studies have reported an increased incidence of type 2 diabetes in GH-treated children (5,6) Although the incidence of type 2 diabetes is low (one case for every 3000 person-years of treatment), monitoring glucose levels before and, periodically, during treatment, has been recommended, especially in subjects with preexisting risk factors, such as obesity, positive family history of type 2 diabetes and pretreatment insulin resistance (5,6).…”
Section: Introductionmentioning
confidence: 99%